Role of the microridges on cactus spines. Issue 2 (17th December 2021) - Guo, Lin; Kumar, Satish; Yang, Mingyang; Tang, Guihua; Liu, Zhigang
Abstract : Microridges on cacti are numerically explored by constructing pyramidal cross sections. Droplet on the designed tri-concave conical fibers moves faster due to the enlarged Laplace pressure difference and decreased contact area. Abstract : Cactus spines have inspired a wide range of micro- and nano-structures that cause droplets to move spontaneously and directionally. The conical shape and the surface wettability gradient are two typical characteristics in such systems. The cross section of the existing conical fibers is usually assumed to be an ideal circle. In fact, microridges are observed on the spine surface of the cactus, and the function is not yet fully understood. The present work thus focuses on how microridges affect droplet self-transport. Structures mimicking microridges are first investigated by constructing pyramidal cross sections with concave or convex lateral faces. The dissipative particle dynamics method is then employed to numerically investigate and theoretically analyze the dynamic behaviors of droplets on these conical fibers with different cross sections. The results show that the microridges reduce the base radius and the contact area of the droplet, thereby increasing the driving force and reducing the friction force. Moreover, by mimicking the microridges structure, we propose a conical fiber with a triple concave cross section, which increases the droplet velocity and the distance traveled over the traditional circular fiber. This work reveals the role of the microridges in the droplet self-transport, which opens up new prospects for the manufacture of fiber systems for microfluidics and liquid manipulation.